Concrete cracking control in underwater marine structures using basalt fiber - Quispe, C. (2021)
The construction of coastal ports requires the use of materials that meet the demands of the marine environment, to prevent underwater concrete structures from cracking and spalling easily; basalt fiber is used to delay the expansion of concrete and prevent the formation of cracks. This research studies the behavior of concrete for prefabricated piles with Portland Cement Type I and basalt fibers added in 0.1%, 0.3% and 0.6%; the results indicate that the fiber is suitable for concrete, the slump decreases, the compressive strength increases for specimens cured in tap water and sea water, the relationship between resistances does not vary, and the depth of carbonation decreases.